The diagnostic value of ictal SPECT—A retrospective, semiquantitative monocenter study. Issue 1 (30th January 2023) - Schulte, Freya; Bitzer, Felix; Gärtner, Florian Christoph; Bauer, Tobias; von Wrede, Randi; Baumgartner, Tobias; Rácz, Attila; Borger, Valeri; von Oertzen, Tim; Vatter, Hartmut; Essler, Markus; Surges, Rainer; et al.
Abstract: Objective: Ictal single photon emission computed tomography (SPECT) can be used as an advanced diagnostic modality to detect the seizure onset zone in the presurgical evaluation of people with epilepsy. In addition to visual assessment (VSA) of ictal and interictal SPECT images, postprocessing methods such as ictal‐interictal SPECT analysis using SPM (ISAS) can visualize regional ictal blood flow differences. We aimed to evaluate and differentiate the diagnostic value of VSA and ISAS in the Bonn cohort. Methods: We included 161 people with epilepsy who underwent presurgical evaluation at the University Hospital Bonn between 2008 and 2020 and received ictal and interictal SPECT and ISAS. We retrospectively assigned SPECT findings to one of five categories according to their degree of concordance with the clinical focus hypothesis. Results: Seizure onset zones could be identified more likely on a sublobar concordance level by ISAS than by VSA (31% vs. 19% of cases; OR = 1.88; 95% Cl [1.04, 3.42]; P  = 0.03). Both VSA and ISAS more often localized a temporal seizure onset zone than an extratemporal one. Neither VSA nor ISAS findings were predicted by the latency between seizure onset and tracer injection ( P  = 0.75). In people who underwent successful epilepsy surgery, VSA and ISAS indicated the correct resection site in 54% of individuals, while MRI and EEG showed the correct resection localization in 96% and 33% of individuals, respectively. It was more likely to become seizure‐free after epilepsy surgery if ISAS or VSA had been successful. There was no MR‐negative case with successful surgery, indicating that ictal SPECT is more useful for confirmation than for localization. Significance: The results of the most extensive clinical study of ictal SPECT to date allow an assessment of the diagnostic value of this elaborate examination and emphasize the importance of postprocessing routines.